Analisis Faktor-Faktor Yang Mempengaruhi Keputusan Pembelian Menggunakan Paylater Pada Mahasiswa Di Kota Makassar - Zigari, Muhammad Baithal Muqaddis; Malik, Anhar Januar; Fadla, Viviet Marjiana; Sulaikah, Helana; Safitri, Wanda Awaliah (Universitas Medan Area, 2023)
This study aims to determine the factors that influence purchasing decisions through the use of the paylater feature. This study uses the Unified Theory of Acceptance and Use Technology (UTAUT) with a quantitative approach. The sampling technique used is purposive sampling. The research data was obtained by distributing questionnaires to students who were studying in Makassar City. The total number of respondents in this study was 46 people. Data analysis techniques used by researchers, namely testing the measurement model and testing the structural model. The results of testing the research data found that performance expectations, effort expectations, and price values do not have a significant influence on purchasing decisions using the paylater feature. The variables of social influence, supporting facilities, hedonic motivation, and habits have a significant effect on purchasing decisions using the paylater feature.